Flow-diverter stenting of post-traumatic bilateral anterior cerebral artery pseudoaneurysm: A case report. Issue 1 (February 2015) - Giorgianni, Andrea; Pellegrino, Carlo; Minotto, Renzo; Mercuri, Anna; Frattini, Lara; Baruzzi, Fabio; Valvassori, Luca
The use of flow-diverter (FD) stents in recent years has positively changed the therapeutic approach to some vascular diseases, especially of certain types of aneurysms. This paper describes the case of a young patient after a major head trauma causing multiple skull fractures. The trauma occasioned two pseudoaneurysms from the A1 segment of the right anterior cerebral artery and from the A2 segment of the left anterior cerebral artery. Both lesions were treated with two Pipeline devices (ev3, Irvine, CA, USA) in two different sessions. The CT study and angiographic investigations performed in the following month showed a complete resolution of the post-traumatic pseudoaneurysmal lesions. Although the use of FD stents is described in the literature, particularly in the treatment of selected aneurysms, this paper shows good technical results in the use of these stents in cases of intracranial post-traumatic pseudoaneurysms with clinical improvement.